Development and initial validation of an instrument to measure students' learning about systems thinking: the affective domain - Camelia, Fanny; Ferris, Timothy L. J.; Cropley, David H. (IEEE, 2015)
The purpose of this study was to develop and validate a new, theoretically-based scale that would assess students' learning about systems thinking in relation to the affective domain in systems engineering education. Students' learning of systems thinking in the affective domain deal with emotions, feelings and valuing the related cognitive systems thinking aspects. It is characterized by belief in the power of systems thinking to enable them to develop superior engineered products and systems. This paper describes the psychometric properties of the scale as the basis for future use with a target population of engineering students. It provides the results of an instrument test analysis of data collected from a representative set of the target audience of the instrument. The participants in this study were 180 undergraduate engineering students who enrolled in a systems engineering course. Exploratory factor analysis of the scale for the sample yielded factors largely consistent with conceptualization and construction of the subscales. Confirmatory factor analysis of the scale also supports the initial factor structure. The results suggest that this instrument may be useful to researchers and practitioners interested in measuring systems thinking in engineering students, particularly in the affective domain.
Keywords: Affective domain; education; systems engineering (SE); SE and theory; SE education; systems thinking